Sailing to and Docking at the Immune Synapse: Role of Tubulin Dynamics and Molecular Motors - Martín-Cófreces, Noa Beatriz; Sánchez-Madrid, Francisco (Frontiers in Immunology, 2018)
The different cytoskeleton systems and their connecting molecular motors move vesicles and intracellular organelles to shape cells. Polarized cells with specialized functions display an exquisite spatio-temporal regulation of both cytoskeletal and organelle arrangements that support their specific tasks. In particular, T cells rapidly change their shape and cellular function through the establishment of cell surface and intracellular polarity in response to a variety of cues. This review focuses on the contribution of the microtubule-based dynein/dynactin motor complex, the tubulin and actin cytoskeletons and different organelles to the formation of the antigen-driven immune synapse.